Management of lumbar disc herniation with radiculopathy: Results of an Iberian-Latin American survey - Quinteros, Guisela (Surg Neurol Int, 2021)
BACKGROUND: Lumbar disc herniation (LDH)/radiculopathy is the most frequent cause of lost workdays in people under 50 years of age. Although there is consensus about how to assess these patients, the optimal management strategy is still debated. METHODS: An online survey was sent to spine surgeons who are members of the Iberian-Latin American Spine Society to assess how they treat LDH with radiculopathy. RESULTS: There were 718 surgeons who answered the survey; 66% reported that 76–100% of their monthly clinic work was due to spine issues. The most frequently used conservative treatment modalities included non-opioid analgesics and nonsteroidal anti-inflammatory drugs (NSAIDs) (90.5%), followed by physical therapy (55.2%) and pregabalin (41.4%). Notably, 40% of surgeons in the public sector believed that conservative treatment failed if symptoms persisted beyond 6–12 weeks, while 39% of private surgeons deemed conservative management insufficient if it had failed to provide symptomatic relief with 3–6 weeks. Of interest, 78% utilized epidural steroid injections (ESI); 51.7% preferred the transforaminal, 27.2% the interlaminar, and 7.5% the caudal approaches. The most frequent indications for surgery included: cauda equina syndrome, progressive neurological deficits, and intractable pain. Traditional microdiscectomy was the most common technique (68.5%) utilized, followed by 7.5% advocating endoscopic disc resection, and just 6.4% favoring the tubular discectomy. CONCLUSION: There is considerable heterogeneity among Iberian and Latin American spine surgeons in the treatment of LDH/radiculopathy. Although most begin with the utilization of NSAIDs and non-opioid analgesics, followed by ESI (88%), surgery was recommended for persistent symptoms/signs for those failing between 3 and 6 weeks (private sector) versus 6–12 weeks (public sector) of conservative therapy.